ZIKATracker: A mobile App for reporting cases of ZIKV worldwide - Alyson Ann Kelvin; David Banner; Luciano Pamplona; Carlos Alencar; Salvatore Rubino; Jorg Heukelbach (Journal of Infection in Developing Countries)
We have developed a mobile App called ZIKATracker (zikatracker.net) to voluntarily be used to report ZIKV cases on a public or private level. As the Zika virus (ZIKV) infection zones are rapidly expanding across South, Central, and North America, and reports have emerged linking ZIKV infection with developmental defects and neurological sequelae, reporting the movement and sequelae of ZIKV is essential. ZIKATracker is a multi-lingual App (English, French, Spanish, and Portuguese) freely available to anyone worldwide wishing to report a suspected or confirmed case of Zika virus and related symptoms. Knowledge gained from the use of this App will help direct the implementation of mosquito control measures in needed areas, bring aid to those affected by the Zika virus, and understand the movement and sequelae of ZIKV as it spreads through communities and across continents.